(untitled) (Nóema, 2021)
Timothy Morton’s philosophical work is set within the framework of the general rethinking of the relationship between the human subject and the environment – and thus of the human itself - which ecological science has been imposing with an ever greater urgency. Since Hyperobjects (2013), however, Morton has joined that broad and heterogeneous trend, often labelled «new materialism», which over the last decade, although in different ways, has increasingly understood this rethinking process as an eminently ontological speculation. According to new materialist perspectives, in other words, a renewed awareness of the mode of being of living beings and of their interconnections generally appears as the main route towards an «ecological» remoulding of subjectivity. Contrary to this ontological approach - and drawing from the critical-deconstructive one developed by Morton in his previous book Ecology Without Nature (2007) - in this article I intend to emphasize the need to ascribe constitutive value, also within the ecological thought, to the epistemic, linguistic and socio-political structures which are distinctive features of the human subject, and above all to the historical dimension which is their common denominator. The friction between Morton’s two texts thus allows us to focus on the inadequacy of every eco-philosophy which holds it possible to rethink the constitution of the human subject simply through the elaboration of a different ontology of the environment.